SOUSVEILLANCE DAN BENTUK-BENTUK BARU PENGAWASAN WARGA NEGARA DALAM DEMOKRASI DIGITAL DI INDONESIA - Puji Rianto (Interaksi: Jurnal Ilmu Komunikasi, 2023)
Amidst the low levels of public trust in public institutions in Indonesia, especially law enforcement agencies, bottom-up monitoring conducted by Indonesian netizens offers new hope for a better democracy. This study examines the forms of bottom-up monitoring, also known as sousveillance, in the context of digital democracy in Indonesia and evaluates their effectiveness in correcting legal violations and promoting justice in society. This study uses a qualitative method. Data was collected through documentation and interviews. Documentation data is analyzed chronologically. The results of the study found that forms of supervision from below or sousveillance provide alternatives and hope for digital democracy in Indonesia. The cases analyzed in this study show how sousveillance is able to correct abuses of power thereby encouraging accountability of public officials and the bureaucracy. Through the use of smartphones and social media, netizens are able to actively participate in supervising public officials. These forms of oversight need to be encouraged in the future to promote a better digital democracy in Indonesia.